Metamaterial and metasurface based emitters for solar thermal photovoltaic applications: analytical review - Lydia Anggraini; Hendra Jaya Tarigan; Joni Welman Simatupang (Institute of Advanced Engineering and Science, 2022)
The motivation behind this paper stemmed from the fact that the world consumes the fast-depleting fossil fuel energy. Before the fossil fuel runs out, new technologies to harvest energy from alternative sources are needed. Sunlight is clean, free and abundant. The market for solar thermal and photovoltaic electricity generation is expanding rapidly. Therefore, an analytical review on the types of emitter for solar thermal photovoltaic (STPV) applications utilizing metamaterials and metasurfaces is presented in this research study. STPV is still important in the development of an emitter technology. STPV classifications based on the types of materials, compositions, dimensions, geometries, and long-term temperature stability are considered. The ability to engineer STPV by controlling one or more of the foregoing physical parameters are useful for researchers. Different types of design and simulation tools are considered. The near future plans are to optimize the efficiency of the emitter and investigate how various layers and different combinations of metamaterials affect such an efficiency by employing a simulation tool such as finite-difference time-domain (FDTD, Lumerical).